REPRESENTATION OF SELF-DEFENSE MECHANISM OF THE MAIN CHARACTER IN THE BLIND SIDE MOVIE - Agita Br Tarigan; Bima Prana Chitra; Hidayati Hidayati (Lembaga Pengembangan Kinerja Dosen, 2022)
This research discussed the self-defense mechanism found in the main character in The Blind Side movie by John Lee Hancock. The writer focused on the analysis of the main character in the movie, named Big Mike. The results of this research indicate that there are several actions taken by the main character towards building self-defense mechanisms. There are eight kinds of self-defense mechanisms in Big Mike's character, namely repression, reaction formation, displacement, rationalization, sublimation, aggression, fantasy, and denial, which represent how Big Mike's character tries to adapt to his new life and protect those closest to him. To achieve the research objectives, the writer uses literary criticism in analyzing Big Mike's character as well as psychological approaches and the theory of self-defense mechanisms proposed by Freud. The primary data for this study was collected from the script and dialogue of The Blind Side movie, which was then analyzed using qualitative methods to reveal various types of self-defense mechanisms contained in the character of Big Mike.